DINAMIKA KOMUNIKASI, LITERASI DIGITAL DAN INKLUSI KEUANGAN DALAM MENENTUKAN PERILAKU KEUANGAN GENERASI HINDU - Suli Asmara; Ida Ayu Nyoman Sutriani; Ida Bagus Made Arjana (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Cirebon, 2025)
Main Purpose - This study aims to analyze the influence of communication dynamics, digital literacy, financial inclusion, financial attitudes, and financial experiences on the financial behavior of the Hindu generation in Mataram. Method - Data were processed using quantitative analysis method with multiple linear regression. The sample in this study was 108 respondents selected using purposive sampling. Main Findings - Communication dynamics and financial inclusion do not significantly impact financial behavior but financial literacy, financial attitudes, and financial experiences significantly influence financial behavior. Communication dynamics fail to exert influence on financial decision-making and behavior although financial institutions provide adequate access (financial inclusion) to financial services, the Hindu generation has yet to fully utilize this access in their financial transactions, resulting in limited benefits. This generation tends to make decisions on saving, borrowing, and spending based on personal history, including their experiences, attitudes, and financial literacy acquired through education, seminars, training, and knowledge from digital sources. Theory and Practical Implications - The implication of this study is to increase Hindu generations awareness of the importance of financial literacy, financial attitudes, and financial experiences in their financial behavior so that they can plan individual finances more carefully in the future. Novelty - The novelty of this research is to examine the influence of communication dynamics variable on the financial behavior of millennial and Z Hindus generations.